Details of the south facing side of the Shikhara (superstructure) - Temples of India Project Team (Jio Institute, 2024)
Details of the south-facing side of the shikhara (superstructure). The cardinal bands of the shikhara have their simulations, known as the urah shringas (miniature shikharas) cascading the mulashrinaga or the main shikhara. The urah shringas have ribbed edges, similar to the mulashringas. Since they diminish in height and emanate out of each other they present a conical cascading effect.